KAJIAN PENINGKATAN USAHA RUMAH TANGGA JAMU HERBAL INSTAN DI DESA GALENGDOWO, WONOSALAM JOMBANG - Richardus Widodo; Tiurma W Susanti Panjaitan (JPM17: Jurnal Pengabdian Masyarakat, 2016)
Traditional herbal drinks until today still exist in Indonesia. Not onlypopular because of its status as Indonesian traditional beverage that isgenerally to maintain health, herbs are also selling consumed for medicinalpurposes. For this reason, many herbal medicine processing business developedby the community. Indonesian biodiversity has approximately 30,000 species ofplants, where 2,500 species of which are medicinal plants. Accordingly,Indonesia legacy of a culture of traditional medicine that has been known for along time and preserved for generations. In fact, various Indonesian herbalproduct has been able to penetrate the world market such as Southeast Asia,East Asia, Europe and America. Herbal products instant already very popularin the cities in East Java, but for medicinal instant production of householdbusinesses of the Village Galengdowo District of Wonosalam Jombang stillcould not penetrate into regional markets given the capacity of the products isstill low and packaging also can not compete with products from Other region.In addition they are also still many find obstacles in terms of marketing andfinancing, when they are ready to expand the marketing area. In this programdeveloping appropriate technology in improving the quantity and quality ofproduct of two household traditional herbal medicine industry. Appropriatetechnology was applied in accordance with the needs of the domestic industry isthe engine of a grater medicinal and herbal instant mixing machine. Moreoverbe efforts to increase the ability of business management, marketing andfinancial management training management, training, marketing managementand financial accounting.Keywords: instant herbal herbs, herbal grater machines, herbal instant mixermachines